Cultural Disabilities of Women Entrepreneurs Field Study of a Sample of Women Entrepreneurs in Bordj Bou Arreridj - belouadah, hassina; makhlouf, nadjeh (Journal of Social Sciences and Humanities, 2024)
The aim of this study is to identify the cultural barriers faced by women entrepreneurs in the province of Bordj Bou Arreridj, using a descriptive approach. The study employed the interview technique by developing an interview guide and conducting interviews with some cases of women artisans at the Traditional Industry Chamber of Bordj Bou Arreridj. The study found that women entrepreneurs in Bordj Bou Arreridj face cultural barriers related to prevailing beliefs about women entrepreneurs and the lack of entrepreneurial training for women. Based on these findings, the study recommends working on enhancing and improving entrepreneurial training for women entrepreneurs in Bordj Bou Arreridj, as well as empowering them socially and culturally. Additionally, it suggests doubling efforts to promote a culture of female entrepreneurship in society in order to reduce cultural obstacles for women entrepreneurs.